Animated Heimlich maneuver education and mothers’ preparedness for toddler choking first aid - Amelia Nurul Hakim; Al Amin (Jurnal Cakrawala Promkes, 2026)
Choking is a life-threatening emergency in toddlers that can lead to hypoxia and death if not promptly managed. Mothers often serve as first responders at home, yet many lack adequate knowledge and appropriate attitudes toward choking first aid. This study evaluated the effect of animated Heimlich maneuver education on mothers’ preparedness to manage choking in toddlers. A pre-experimental one-group pretest–posttest design was conducted among 86 mothers of children aged 1–3 years at Pamulang Community Health Center, recruited through consecutive sampling. Knowledge and attitudes were assessed using structured questionnaires before and after a 6-minute animated video intervention demonstrating choking risks, signs, and the Heimlich maneuver. Data were analyzed using the Wilcoxon signed-rank test. Results showed significant improvements in both knowledge and attitudes. The proportion of mothers with good knowledge increased from 18.6% to 72.1%, and positive attitudes increased from 30.2% to 90.7%. These changes were statistically significant (knowledge: Z = −8.214, p < 0.001; attitudes: Z = −8.342, p < 0.001). Animated education on the Heimlich maneuver effectively improves mothers’ knowledge and attitudes toward choking first aid and offers a practical strategy to enhance caregiver preparedness.